2013
DOI: 10.1186/1757-7241-21-71
|View full text |Cite
|
Sign up to set email alerts
|

Flexible fixation of syndesmotic diastasis using the assembled bolt-tightrope system

Abstract: BackgroundSyndesmotic diastasis is a common injury. Syndesmotic bolt and tightrope are two of the commonly used methods for the fixation of syndesmotic diastasis. Syndesmotic bolt can be used to reduce and maintain the syndesmosis. However, it cannot permit the normal range of motion of distal tibiofibular joint, especially the rotation of the fibula. Tightrope technique can be used to provide flexible fixation of the syndesmosis. However, it lacks the ability of reducing the syndesmotic diastasis. To combine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…More recently, the suture-button fixation device has aroused the attention of many orthopedists, especially TightRope. This device has been reported with some potential advantages, such as allowing of physiological movement while retaining the required reduction, less risk of implant removal and recurrent syndesmotic diastasis, and earlier rehabilitation [ 8 10 ]. Anatomic reduction has been shown to be the most important predictor of clinical outcomes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the suture-button fixation device has aroused the attention of many orthopedists, especially TightRope. This device has been reported with some potential advantages, such as allowing of physiological movement while retaining the required reduction, less risk of implant removal and recurrent syndesmotic diastasis, and earlier rehabilitation [ 8 10 ]. Anatomic reduction has been shown to be the most important predictor of clinical outcomes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical applications revealed that ABTS could reduce the syndesmotic diastasis and provide flexible fixation in a bionic fashion followed with satisfactory functional recovery of the lower extremities. [ 8 ] Orthopedic surgeons have also created many other novel bionic designs. However, some of these designs have been hindered from the clinical application due to the limited manufacturing capability of complex internal implants.…”
mentioning
confidence: 99%
“…Several repair techniques for syndesmotic injury of the ankle are available, including 1- and 2-screw techniques; stainless, titanium, and bioabsorbable screw techniques; modified syndesmotic bolt repair; suture button repair; and assembled bolt-suture button system repair. 1,2,13,14,18-21 However, there is no “gold standard” technique, and the optimal method of syndesmotic fixation remains a topic of debate. All of the above-listed techniques have advantages and disadvantages: for example, in the stainless and titanium screw fixation techniques, late syndesmotic widening following screw removal, and screw loosening, screw breakage, the need for a second operation to remove the screw, and morbidity associated with prolonged immobilization, are all possible outcomes.…”
Section: Discussionmentioning
confidence: 99%